An Analysis of Higher Order Thinking Skills (HOTS) in the Reading Exercises of the Textbook “English for Nusantara” for the Eighth Grade of Junior High School Based on Bloom's Taxonomy - Zebua, Feliks Rejeki Sotani; Harefa, Trisman; Maru'ao, Nursayani; Zega, Riswan (Journal of English Language and Education, 2025)
Higher Order Thinking Skills (HOTS) are essential in developing students’ critical and analytical abilities, particularly through reading activities. Many English textbooks still lack adequate integration of HOTS-based tasks, creating a gap between curriculum expectations and actual practice. This study aimed to analyze the distribution of HOTS in the reading exercises of the “English for Nusantara” textbook for eighth grade junior high school students. Employing a descriptive qualitative method and content analysis, data were collected from five chapters of the textbook used at SMP Negeri 1 Gunungsitoli Barat. A checklist based on Bloom’s Taxonomy was used to identify HOTS elements. The findings revealed that only 23 out of 116 reading exercises (19.6%) contained HOTS components. The most common skill was analyzing (C4), followed by creating (C6) and evaluating (C5). These results indicate limited integration of HOTS in the textbook, which highlights the need for improvement in English instructional materials.